Nepal : First Review of Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report, 2004)
This paper focuses on Nepal's First Review of the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) and Request for Waiver of Performance Criteria. The difficult political and security situation notwithstanding, the PRGF-supported program is broadly on track. All quantitative targets for the first review were met, and all structural reform measures are expected to be implemented by the Board date, although some actions were completed after the target dates. For 2003/04, real GDP growth is estimated at 3 1\2 percent, in line with the program.